Interplays of Interfacial Forces Modulate Structure and Function of Soft and Biological Matters in Aquatic Environments - Tanaka, Motomu (Frontiers in Chemistry, 2020)
Water had been considered as a passive matrix that merely fills up the space, supporting the diffusion of solute molecules. In the past several decades, a number of studies have demonstrated that water play vital roles in regulating structural orders of biological systems over several orders of magnitude. Water molecules take a versatile of structures, many of which are transient. Water molecules act as hydrogen bond donors as well as acceptors and biochemical reactions utilize water molecules as nucleophiles. Needless to say, the same principle holds for the synthetic materials that function under water: the conformation, dynamics and functions of molecules are significantly influenced by the surrounding water. This review sheds light on how the structure and function of soft and biological matter in aquatic environments are modulated by the orchestration of various interfacial forces.